2014
DOI: 10.7774/cevr.2014.3.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and efficacy of a plasmid DNA rabies vaccine incorporating Myd88 as a genetic adjuvant

Abstract: PurposeMyeloid differentiation factor 88 (Myd88), a ubiquitous Toll-like receptor adaptor molecule, has been reported to play important roles in B cell responses to infections and vaccination. The present study evaluated the effects of genetic adjuvanting with Myd88 on the immune responses to a plasmid DNA rabies vaccine.Materials and MethodsPlasmids encoding rabies glycoprotein alone (pIRES-Rgp) or a fragment of Myd88 gene in addition (pIRES-Rgp-Myd) were constructed and administered intramuscularly or intrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…An alternative to using TLR ligands is the expression of proteins which mediate signaling directly downstream of activated TLRs. This was tested by incorporating two genes, MyD88 and TRIF, into DNA-vaccine plasmids against influenza or rabies [ 72 , 73 ]. Both genetic adjuvants were able to enhance the resulting immune responses.…”
Section: Genetic Adjuvantsmentioning
confidence: 99%
“…An alternative to using TLR ligands is the expression of proteins which mediate signaling directly downstream of activated TLRs. This was tested by incorporating two genes, MyD88 and TRIF, into DNA-vaccine plasmids against influenza or rabies [ 72 , 73 ]. Both genetic adjuvants were able to enhance the resulting immune responses.…”
Section: Genetic Adjuvantsmentioning
confidence: 99%
“… 14 showed that a DAI-expressing plasmid can be efficiently used as a genetic cancer vaccine inducing memory and effector tumor-specific T-cells. Similarly, myeloid differentiation factor 88 (MyD88), a ubiquitous Toll-like receptor adaptor molecule, has been used as a genetic adjuvant to harness intrinsic immune-stimulating properties of a DNA vaccine 15 and a MyD88-encoding adenovirus was shown to potentiate local and systemic antitumor immunity. 16 …”
Section: Introductionmentioning
confidence: 99%
“…The principle of DNA vaccines has been confirmed for rabies virus in small animal models in which they demonstrate immunogenicity [18], but this has not translated into effective vaccines in larger animals, and they are poorly immunogenic in humans [19]. Further, there is concern, so far with no supporting evidence, that exogenous DNA could be incorporated into the host genome.…”
Section: Dna Vaccinesmentioning
confidence: 99%